O imaginário em narrativas da literatura infantojuvenil amazonense - Sicsú, Delma Pacheco (2013)
The objective of this work is to address the ,literary imaginaryin Amazonian Children and Youth Literature,taking nineteennarratives asobject of analysis. The nineteen narratives were written by Elson Farias, Zemaria Pinto, Thiago de Mello, Wilson Nogueira, Roní Wasiri Guará, Jaime Diakara and Yaguarê Yamã. This current work comes from the need to investigate Children and Youth Literature because of the fact that this literature is not well know nand does not have academic research. The research will take the literary imaginary as a theoretical assumption for consideringit avast field of investigation around the symbols found in literature, which does not end, because it considers its manifestatio nand significance according to the historical and cultural context to whichit belongs. Therefore, its basis will be theoretical studies that consider the imaginary as something not closed, but as an open field of investigation that will receive new meaning according to the cultural context to which it belongs. Besides the imaginary, this research also deals with electronic support, in particular the website as a means to archive, promote and criticize Amazonian Children and Youth Literature. The aim of this research is to contribute not only to a better understanding of how the literary imaginary manifests in Amazonian Children and Youth literature, but also to contribute to the construction of an archive that can protect this literature, which is as important as the Amazonian literature intended for adult audiences. Theoretical support for this research will be the studies of Bachelard (1993), Durand (2002), and Trinidad and Laplatine (1997), Levy (1996) and others who maycontribute to the current study. This research proposal is believed tobe relevant because besidesstudying theliterary imaginaryin Amazonian Children and Youth Literature, it also intends to archive it in order tooffer futureresearchersa source ofresearch on it. Keywords: Imaginary, AmazonianChildren and Youth Literature, Electronic support.